Pemilihan Alternatif Investasi Dana Haji dalam Mendorong Pertumbuhan Ekonomi: Pendekatan Analytic Network Process (ANP) - Abdul Ghofar; Achmad Firdaus; Ronald Rulindo (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study aims to analyze the criteria for investing in Hajj funds and alternative investments that provide benefits to Muslims so that they have an impact on economic growth. By using the Analytic Network Process (ANP) approach, alternative investments offered are Infrastructure, Property, Financial Sector, and Real Sector. Data were collected using a questionnaire consisting of pairwise comparisons between groups and their assessment indicators. A total of 7 (seven) expert speakers (experts) who became respondents successfully collected and processed using the ANP method. The results showed that investment in infrastructure and the real sector provides benefits to Muslims economically, so as to improve the welfare of Muslims which in turn can encourage economic growth